A Review of Non-wood Lignocellulose Waste Material Reinforced Concrete for Light-weight Construction Applications - Saeed H.S.S.; Syamsir A.; Bakar M.S.A.; Najeeb M.I.; Alhayek A.; Itam Z.; Asyraf M.R.M.; Ali M.R. (Universiti Putra Malaysia Press, 2025)
In recent decades, non-wood lignocellulosic materials have gained significant attention, particularly in concrete applications for construction purposes. This study delves into utilising non-wood lignocellulosic materials for reinforcing concrete in construction applications. Lignocellulosic material emerges as a promising option for formulating new fibre cement compositions, thereby enhancing the sustainability, affordability, and performance of construction materials. Moreover, this research broadens the horizons of recycling agricultural waste by facilitating rational disposal and optimal utilisation. Through a comprehensive review, the study reveals that flax fibres, coir pith, prickly pear fibres, and rice husk ash waste exhibit superior workability compared to their counterparts. Furthermore, the strength of non-wood lignocellulosic reinforced concrete, incorporating bagasse ash, rice husk ash, and nutshell ash, peaked when fine aggregate replacement reached 15%, surpassing other types of non-wood lignocellulosic reinforced concrete. Adding a small quantity of prickly pear fibre to cement enhances the thermal conductivity of concrete, consequently improving compressive strength, flexural strength, tensile strength, and elastic modulus. This research is relevant to international research as it advances sustainable construction materials with desirable properties, benefiting society and various industries. ? Universiti Putra Malaysia Press.